Continental crust recycling in collisional zones: insights from Li isotope compositions of the syn-exhumation and post-collisional mafic magmatic rocks - Sun, Guo-Chao; Zhao, Zi-Fu; Dai, Li-Qun; Chen, Ren-Xu; Chen, Long (Frontiers in Earth Science, 2024)
Syn-exhumation and post-collisional mafic magmatism in continental collision orogenic belts may provide insights into the nature of orogenic lithospheric mantle and recycled continental components in continental subduction zones. Lithium and its isotopes have emerged as potentially valuable tools for shedding light on the origin of these magmas, given the contrast Li contents and isotopic compositions between the subducting continental crust and the mantle. Here, we present high-precision Li isotopes data for representative orthogneiss, continental eclogite, syn-exhumation and post-collisional mafic magmatic rocks from the North Qaidam orogen. The synexhumation mafic magmatic rocks have relative higher Li contents (26.5-50.0 ppm) and lower δ 7 Li values (-1.01-1.48 ‰) than those of the post-collisional mafic magmatic rocks (Li = 11.1-22.7 ppm, δ 7 Li = 1.20-3.38 ‰), which are comparable to those of orthogneiss and continental eclogite, respectively. Dehydration and melting modelling results show that these mafic magmatic rocks have similar Li contents and δ 7 Li values to the continental eclogite-and orthogneiss-derived melts but are different from their derived fluids. Monte Carlo simulation for Li-Nd isotopes suggests the syn-exhumation and post-collisional mafic rocks could be derived from an enriched mantle source that contains 3-8 % continental crustal components dominated by the orthogneiss and continental eclogite. The calculated results are consistent with the results from the previous study simulated by trace elements. Therefore, our results highlight Li isotopes as a potential tool to trace the nature of the continental crustal components recycling in continental subduction zones.